2015
DOI: 10.1007/s11771-015-2761-x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and disaster prevention for catastrophic fire airflow of main air-intake belt roadway in coal mine—A case study

Abstract: Coal mine belt fire develops very rapidly and is difficult to control. If not suppressed quickly, a belt fire could easily lead to airflow disorder and undermine the ventilation system. However, belt fire can be prevented effectively by establishing fire airflow control system. In this work, the 5th belt roadway of Kongzhuang coal mine was taken as the object of investigation, where geometrical models of this roadway were established firstly. Then, based on mathematical model of fire smoke flow, the CO volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Mine exogenous fire has the characteristics of sudden occurrence and serious damage, which had killed dozens (or even hundreds) of miners worldwide. 1,2 The main factor for the heavy casualties is the spread of the smoke stream generated by the fire in the ventilation network. 3 Owing to the underground tunnel environment, narrow spaces, and complicated ventilation network, serious secondary disasters can be caused by disasters combining with each other.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mine exogenous fire has the characteristics of sudden occurrence and serious damage, which had killed dozens (or even hundreds) of miners worldwide. 1,2 The main factor for the heavy casualties is the spread of the smoke stream generated by the fire in the ventilation network. 3 Owing to the underground tunnel environment, narrow spaces, and complicated ventilation network, serious secondary disasters can be caused by disasters combining with each other.…”
Section: Introductionmentioning
confidence: 99%
“…16 A mine fire relief decision support system was developed and applied in the coal mine. 2 The casualties caused by fire accidents in coal mines over the last 5 years are shown in Table 1. ters should be further revealed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two rows of anti-slide piles are arranged at the front and the back of the landslide, and they are connected by a beam to form a spatial anti-sliding structure with a beam-column combination. In [7][8][9][10][11][12], engineering examples, model tests, theoretical calculations, and numerical simulation studies have shown that gate-type anti-sliding piles are relatively rigid. Under the action of tie beams, the front and rear rows of piles jointly assume the landslide thrust and the Earth pressure around the pile effectively reduces the horizontal displacement of the pile, so that more landslide thrust is transmitted to the stable (anchor section) below the sliding surface through the axial force, so the gate type anti-slide pile limits the deformation of the slope.…”
Section: Introductionmentioning
confidence: 99%